2020
DOI: 10.3389/fneur.2020.00136
|View full text |Cite
|
Sign up to set email alerts
|

Single vs. Combined Therapeutic Approaches in Rats With Chronic Spinal Cord Injury

Abstract: The regenerative capability of the central nervous system is limited after traumatic spinal cord injury (SCI) due to intrinsic and extrinsic factors that inhibit spinal cord regeneration, resulting in deficient functional recovery. It has been shown that strategies, such as pre-degenerated peripheral nerve (PPN) grafts or the use of bone marrow stromal cells (BMSCs) or exogenous molecules, such as chondroitinase ABC (ChABC) promote axonal growth and remyelination, resulting in an improvement in locomotor funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
0
9
0
1
Order By: Relevance
“…It was also observed that animals, after 2 months of PPN and MSC transplants in a full-section model, had a greater number of growing axons by detecting GAP43 as well as an improvement in remyelination by detection of PBM and by electron microscopy, unlike animals treated with simple transplantation [88]. When making a triple combination of PPN with MSCs and ChABC, an increase in axonal regeneration was observed after 3 months, improving locomotor function [89].…”
Section: Combined Treatmentsmentioning
confidence: 95%
“…It was also observed that animals, after 2 months of PPN and MSC transplants in a full-section model, had a greater number of growing axons by detecting GAP43 as well as an improvement in remyelination by detection of PBM and by electron microscopy, unlike animals treated with simple transplantation [88]. When making a triple combination of PPN with MSCs and ChABC, an increase in axonal regeneration was observed after 3 months, improving locomotor function [89].…”
Section: Combined Treatmentsmentioning
confidence: 95%
“…On the other hand, perhaps the best known (and also the most controversial) contribution of IMSS neuroscientists is the treatment of advanced Parkinson's disease with adrenal medulla autologous transplantation 60,61 . Experimental and clinical studies on traumatic spinal cord injury pathophysiology and surgical and pharmacological treatment are carried out at this same Unit [62][63][64] .…”
Section: Neurological Diseasesmentioning
confidence: 99%
“…However, some regeneration potential is present after SCI; indicating that a permeable and replacement microenvironment occurs at the site of injury. It can activate proteins such as growth-associated protein 43 (GAP-43) or microtubule-associated protein (MAP)1B that initiate axonal growth, but this is insufficient to generate new connections, due to the physical barrier at the injury site [55].…”
Section: Effect Of Aldynoglia Cells On Regeneration After Scimentioning
confidence: 99%